PLEKHA5 as a Biomarker and Potential Mediator of Melanoma Brain Metastasis - Jilaveanu, Lucia B. (Clin Cancer Res, 2014)
PURPOSE: Approximately 40% of metastatic melanoma patients develop brain metastases. Our purpose was to identify genes aberrantly expressed in melanoma that might be associated with propensity for brain homing. EXPERIMENTAL DESIGN: We studied gene expression profiles in a cell line model of brain metastasis (cerebrotropic A375Br cells versus parental A375P cells) and compared them to profiles of patients who developed early brain metastases and who did not. A tissue microarray containing 169 metastatic melanoma cases with variable time to brain metastasis was constructed to further study marker expression by quantitative immunofluorescence. An in vitro model of the blood brain barrier (BBB) was generated to evaluate potential mediators of brain metastases. RESULTS: PLEKHA5 was differentially expressed in both the A375 cell line model and patient samples subjected to gene expression profiling. At the protein level, by quantitative immunofluorescence, PLEKHA5 was associated with decreased brain metastasis free survival. PLEKHA5 over-expression was not associated with other metastatic sites. Knock-down of PLEKHA5 decreases viability of A375Br cells, inhibits BBB transmigration and invasion in vitro. Similar results were found with YUMUL cells, cultured from a patient with overwhelming brain metastases. PLEKHA5 knock-down did not affect the viability of A375P cells. CONCLUSIONS: PLEKHA5 expression in melanoma tumors was associated with early development of brain metastases. Inhibition of PLEKHA5 might decrease passage across the BBB and decrease proliferation and survival of melanoma cells both in the brain and in extra-cerebral sites.